In Situ Construction of Flexible Low‐Dimensional van der Waals Material Photodetectors - Chen, Yu; Liang, Huanrong; Guan, Xinyi; Ma, Yuhang; Zheng, Zhaoqiang; Ma, Churong; Du, Chun; Yao, Jiandong (Advanced Physics Research, 2025)
By virtue of the excellent flexibility, conformability, portability, and aesthetics, wearable photodetectors have attracted worldwide research enthusiasm over the past decade. However, traditional bulk covalent semiconductors are difficult to be applied to wearable photodetectors due to their pronounced rigidity. Profiting from the self‐passivated surface, excellent carrier mobility, and strong light‐harvesting ability, low‐dimensional van der Waals materials (LDvdWMs) have shown immense potential for application in wearable optoelectronic devices. Nevertheless, the preparation of flexible photodetectors through exfoliation/transfer or solution methods has suffered from severe drawbacks spanning low production yield, severe contamination, and uncompetitive device properties. Therefore, researchers have been committed to exploring alternative preparation strategies. In response to this, the current review systematically summarizes the latest research advancements in directly constructing LDvdWM photodetectors on flexible substrates, including developing low‐melting‐point targeted materials, electron‐beam‐enabled crystallization, photonic crystallization, modified chemical vapor deposition, and pulsed‐laser deposition, with the elaboration on the fundamental mechanisms enabling in situ deposition of LDvdWMs. Finally, the tricky challenges standing in the way in this field have been epitomized and potential solutions addressing them have been proposed. On the whole, this review underscores distinctive pathways for the development of flexible LDvdWM photodetectors, which probably usher in next‐generation wearable optoelectronic technologies. This review summarizes the progress in directly constructing low‐dimensional van der Waals material photodetectors on flexible substrates, including developing low‐melting‐point materials, electron‐beam‐enabled crystallization, photonic crystallization, modified chemical vapor deposition, and pulsed‐laser deposition, with a keen eye on fundamental mechanisms. Finally, prevalent challenges have been epitomized and potential solutions have been proposed, providing new pathways for next‐generation wearable technologies.